Selective contrast-enhanced computed tomography is appropriate in diffuse large B-cell lymphoma therapy response assessment - Kriegsmann, Katharina; Wack, Maurizio; Kriegsmann, Mark; Cremer, Martin; Bruckner, Thomas; Ho, Anthony Dick; Wuchter, Patrick; Witzens-Harig, Mathias (European journal of haematology, 2018)
Objective Although not the gold standard, contrast-enhanced CT of neck, thorax, and abdomen/pelvis is routinely performed in diagnosis and response assessment of DLBCL. PD during first-line treatment is a relatively rare event. The question arises if the imaging of initially involved regions only might be sufficient for response evaluation. Method We retrospectively analyzed the data of 167 DLBCL patients who had an extensive contrast-enhanced CT scan at first diagnosis. The majority of patients (n = 128, 77%) was treated with R-CHOP. Therapy response was assessed as interim and end of treatment staging by contrast-enhanced CT. Results The overall response rate at the end of treatment was 94%. None of the patients showed involvement of new sites at interim staging. As a major finding, none of the patients showed an involvement of sites, which were not initially involved. Four patients developed PD during first-line chemotherapy/after mid-treatment staging and 31 relapsed. A conclusive comparison between initial and PD/relapse DLBCL involvement was possible in 27 patients: 8 patients did and 19 patients did not show additional/new sites of involvement compared to first diagnosis. Conclusion Our retrospective analysis provides a rationale for selective imaging of initially involved DLBCL sites for therapy response assessment.